Tantangan Organisasi Pendidikan Islam di Era Brittle, Anxious, Non-Linear, Incomprehensible (BANI) - Farid, Ahmad; Susanto, Susanto (Indo-MathEdu Intellectuals Journal, 2026)
Islamic education today stands at a crossroads between preserving tradition (al-turāts) and the demands of modernity (al-ḥadītsah). Entering the third decade of the 21st century, the challenges faced have evolved from the VUCA era to the BANI era (brittle, anxiety, non-linear, incomprehensible), which is characterised by uncertainty and high complexity. These conditions require Islamic educational institutions to have organisational resilience so that they do not experience entropy or systemic decline. This study aims to describe the organisational strategies of Islamic education in facing the challenges of the contemporary era through the Systems Theory and Contingency Theory approaches. The research method used is a literature study with a descriptive-critical analysis design. The results of the study indicate that, from the perspective of Systems Theory, Islamic educational organisations need to function as open systems that integrate Islamic values as a spiritual anchor with the use of modern technology, such as the Internet of Things (IoT) and artificial intelligence, as a new source of energy (negative entropy). Meanwhile, Contingency Theory emphasises the importance of situational and flexible managerial adaptation, including a shift from rigid bureaucratic structures to more organic and responsive structures through the mechanism of shura. The synthesis of these two approaches gives rise to the concept of managerial tajdīd, which balances the stability of transcendental values with operational agility to produce relevant insan kāmil in the digital age